PENGARUH PEMANFAATAN SOSIAL MEDIA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS KELAS X DI SMK NEGERI 1 BITUNG - ., Seinca; Kambey, Joseph P.; Winokan, Amsje (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the effect of social media utilization and learning motivation on the learning outcomes of office management and business service class X students at SMK Negeri 1 Bitung. This study uses a quantitative approach and uses primary data through distributing questionnaires to 75 office management and business service class X students at SMK Negeri 1 Bitung. The results of the study obtained a multiple linear regression equation Ŷ = 5.011 + 0.546 X₁ + 0.405X₂. learning motivation has a significant effect on learning outcomes with a t-count value> t-table, namely (6.800> 1.993). Then the results of the F test prove that the use of social media and learning motivation simultaneously have a significant effect on the learning outcomes of office management and business service class X students at SMK Negeri 1 Bitung with an F-count value greater than the F-table, namely (557.18> 3.12) with a significance value of 0.000 <0.05. The conclusion is that the use of social media and learning motivation have a significant effect both partially and simultaneously on the learning outcomes of office management and business services students of class X at SMK Negeri 1 Bitung. Keywords: Use of Social Media, Learning Motivation, Learning Outcomes